The efficacy of three hand asepsis techniques using chlorhexidine gluconate (CHG 2%) - Cunha, Érika Rossetto da; Matos, Fabiana Gonçalves de Oliveira Azevedo; Silva, Adriana Maria da; Araújo, Eutália Aparecida Cândido de; Ferreira, Karine Azevedo São Leão; Graziano, Kazuko Uchikawa (Revista da Escola de Enfermagem da USP, 2011)
The scrubbing of hands and forearms using antiseptic agents has been the standard pre-operative procedure to prevent surgical site infection. With the introduction of antiseptic agents, the need to use brushes for pre-operative disinfection has been questioned and it has been recommended that the procedure be abandoned due to the injuries it may cause to the skin. With the purpose to provide the foundations for the efficacy of pre-operative asepsis without using brushes or sponges, the objective of this study was to evaluate three methods of pre-operative asepsis using an antimicrobial agent containing chlorhexidine gluconate - CHG 2%; hand-scrubbing with brush (HSB), hand-scrubbing with sponge (HSS), and hand-rubbing with the antiseptic agent (HRA) only. A comparative crossover study was carried with 29 healthcare providers. Antimicrobial efficacy was measured using the glove-juice method before and after each tested method. Statistical analyses showed there were no significant differences regarding the number of colony-forming units when comparing HRA, HSB, and HSS techniques (p=0.148), which theoretically disregards the need to continue using brushes or sponges for hand asepsis.